Supplementation with medium-chain fatty acids increases body weight loss during very low-calorie ketogenic diet: a retrospective analysis in a real-life setting - Claudia Vetrani; Ludovica Verde; Silvia Savastano; Annamaria Colao; Giovanna Muscogiuri; Luigi Barrea (Journal of Translational Medicine, 2023)
Abstract Background Very low-calorie ketogenic diet (VLCKD) has shown to significantly reduce body weight and fat mass, as well as inflammation. These effects are supported by nutritional ketosis, which triggers the utilization of the ketone body as an energy source. Medium-chain fatty acids (MCTs) might serve as potential enhancers of ketone bodies production with a greater effect on weight loss. Nevertheless, no clinical studies have evaluated the effect of MCTs supplementation in addition to VLCKD. Therefore, the present study aimed to evaluate whether the supplementation with MCTs can induce a greater weight reduction during the ketogenic phase of VLCKD. Methods In this retrospective study, 263 women with overweight/obesity (body mass index, BMI: 35.7 ± 5.3 kg/m2) aged 37.5 ± 14.2 years followed one of these dietary protocols for 45 days: (a) Control group, 83 participants (31.6%) (VLCKD without MCTs), (b) VLCKD + MCTs group, 86 participants (32.7%) (MCTs supplementation − 20 g/day- during VLCKD starting from the first day of the active phase), (c) VLCKD + earlyMCTs, 94 participants (35.7%) (MCTs supplementation − 20 g/day-starting from 5 days before the beginning of the VLCKD active phase. Anthropometric measures, body composition, and c-reactive protein (CRP) concentrations were collected at the beginning and at the end (45 days) of the VLCKD intervention. Results MCTs supplementation significantly decreased body weight, BMI, and waist circumference as compared to the control group, with a greater effect in the VLCKD + earlyMCTs group. A two-fold decrease in fat mass and an increase in muscle mass were observed in the VLCKD + earlyMCTs group as compared to the control group. As for inflammation, hs-CRP concentrations (assessed as absolute percent change) were significantly lower in the VLCKD + MCTs group (p = 0.009) and the VLCKD + earlyMCTs group (p = 0.011) than in the control group. A logistic regression model showed that VLCKD + earlyMCTs increase the likelihood of improvement of BMI classes (OR: 1.85, 95% CI 1.02–3.36) also after adjusting for the potential confounding factors. Conclusion MCTs supplementation (20 g/day) may be a useful tool to enhance the beneficial effect of VLCKD on the reduction of body weight and fat mass. In particular, MCTs supplementation before the beginning of the VLCKD active phase might facilitate ketosis thus contributing to the effectiveness of the nutritional intervention.